Digital Inequality Across Major Life Realms. (August 2018) - Robinson, Laura; Chen, Wenhong; Schulz, Jeremy; Khilnani, Aneka
This issue of the American Behavioral Scientist probes digital inequality as both an endogenous and exogenous factor shaping key life realms and social processes. These include aging and the life course, family and parenting, students and education, prisoner rehabilitation, and social class. The relationships between digital inequality and these life realms are explored in different institutional and national contexts. By drawing connections between digital inequality and these distinct—yet interconnected—life realms, this issue marks a new frontier in the study of digital inequality.